Analysis of collaborative governance regime in spatial and zone planning policy in greater Malang area / Siti Khodijah Ananda Ayu ... [et al.] - Ananda Ayu, Siti Khodijah; Shavila, Rerica Dhea; Irhamna, Muhammad Hafizh (2021)
Collaboration in governance is necessary to create synergy in development between adjacent regions. This aims to achieve acceleration in certain sectors as a form of joint problem solving. In addition, it is also necessary to harmonize policies between adjacent regions so that they do not overlap. Regional development is supported by PAD (Local Government Revenue) which indicates what the community needs and what to provide public services wise. One of the development synergies between adjacent regions is the Greater Malang area which consists of City of Malang, Malang Regency, and City of Batu. To paint a picture of the phenomenon of increasing development in the Greater Malang area, it can be seen through PAD data from BPS (Central Bureau) for 2018-2019, PAD Malang Regency in 2018 amounted to 3,826.7 billion and in 2019 amounted to 4,107.72 billion. Meanwhile, City of Malang' PAD in 2018 reached 2,040.19 billion and in 2019 totaled 2,247.76 billion. Lastly, PAD of City of Batu in 2018 amounted to 985.25 billion and in 2019 it reached 990.15 billion. This demonstrates an increase of regional revenue in line with the addition of infrastructure development. To achieve a balanced development, it is not only seen from additional investment standpoint, but also the need to adhere to environmental impacts. Therefore, to administer development that is not in accordance with its designation, it can be minimized through spatial zoning plans. One form of its regulations can be seen through spatial and regional planning.